As relações de autoridade na escola e na família segundo os adolescentes - Pereira, Elaine Aparecida (2014)
This research paper, empirical in nature, aims to analyze the relationship adolescents in the 9th grade of Elementary School develop towards authority exercised over them, in school and in their families, as well as their understanding of authority. The research was conducted in two local government-run schools in São Paulo, both located in regions having a low Human Development Index (HDI), even though their scores on the Index for Basic Education Development (IDEB) differed. The focus group was used in the data collection procedure, along with a questionnaire containing open-ended and close-ended questions. The subjects under study consisted of twelve students - six girls and six boys in the 9th grade of Elementary School. For the purpose of this research paper, ideas taken from authors of the critical theory on authority were used for its theoretical framework. The writings of Horkheimer and Marcuse contributed towards situating the concept of authority in modern days, through the relationship it establishes with the concept of individual freedom in a bourgeois philosophy. Also based on these authors, the role of the family is discussed as an institution responsible for developing certain requirements of social behavior in individuals. Based on the ideas of Adorno, the concepts of training, enlightened and non- enlightened authority are discussed, as well as taboos applying historically to teaching. The study was developed based on two hypotheses: 1) the authority exercised by adults over adolescents is reduced to an authoritarianism expressed by uncritical demands for observance of rules and obedience, and an indifference on the part of adolescents to that which is imposed on them; and 2) the authority exercised by adults is not able to develop independence in adolescents, but is limited to their adapting to the reality imposed on them by the structure of society. The results of this research work indicate that adolescents are in a position of heteronomy where the authority exerted on them, both at school and within the family is concerned, and that they value and crave for authority even when it is manifested in the form of authoritarianism; moreover, the authority exercised on them by institutions is legitimized by adolescents, since it is considered an important contribution towards their training and adaptation to the requirements of society